(untitled) (Bridging Cultures, 2021)
Mental health can have an impact on several vital areas, including but not limited to work, studies or relationships. This paper examines the relationship between mental health issues –such as stress or anxiety– and college students, focusing on the perception of stress that students have in connection to exams, deadlines or time management, among others. For this end, a survey was carried out among a small group of English students (both in Translation and Teacher Training courses) at Universidad Catoílica Argentina to measure their perceived feelings of stress and to question them about the support systems available to them at the aforementioned university. Both the survey and the literature cited in the paper seem to reinforce the conclusion that mental health issues are relevant in academic contexts and may be connected to a variety of factors including academic pressures, test anxiety and bad time management.